Influence of New Technologies on Customer Relationship Management - Markus H. NIEDERMAYER; Monika ZATROCHOVÁ (Communications of International Proceedings, 2021)
This paper deals with the topic that business processes are in an increasing digitalisation. There is an increasing dependence on the quality of data, which is in contrast to the increasing awareness of data security. In this context, new systems supported by artificial intelligence are coming into use, where it is difficult for the individual user to distinguish whether he is still dealing with a human counterpart or with a well-programmed algorithm. However, the circumstances presented in this paper will lead to the need to question existing CRM systems and to integrate the new possibilities and risks into the consideration. However, automated customer interaction controlled by algorithms is no longer conceivable without operational systems for reasons of effectiveness and above all for cost reasons.
Keywords: CRM-Systems; data-driven technology; data collection